2017
DOI: 10.4103/ijmbs.ijmbs_59_17
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, physiological and body composition changes in patients with type 2 diabetes during Ramadan fasting

Abstract: The month of Ramadan, the 9 th month of the Islamic lunar calendar, is a holy month in the Muslim religion. During this period, Muslims must fast from dawn until sunset. The Holy Qur'an specifically exempts people with a medical reason from observing the fast, especially if this can have negative consequences on their health. [1] During the fasting, diabetic patients, because of their pathology, are exposed to an increased risk of hypoglycemia, loss of diabetes control, dehydration (especially in summer) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
3
10
0
Order By: Relevance
“…Although the current study did not detect significant differences in the participants' activities between periods, physical activity during Ramadan was slightly higher than in the after Ramadan period. A similar finding has been reported by Sfar et al [58], who showed a non-significant increase in physical activity of Tunisian individuals with T2DM during Ramadan compared to the pre-Ramadan period. In addition, the total activity measured by IPAQ showed a significant increase during Ramadan in this study compared to the after Ramadan period, but with small effect size.…”
Section: Discussionsupporting
confidence: 90%
“…Although the current study did not detect significant differences in the participants' activities between periods, physical activity during Ramadan was slightly higher than in the after Ramadan period. A similar finding has been reported by Sfar et al [58], who showed a non-significant increase in physical activity of Tunisian individuals with T2DM during Ramadan compared to the pre-Ramadan period. In addition, the total activity measured by IPAQ showed a significant increase during Ramadan in this study compared to the after Ramadan period, but with small effect size.…”
Section: Discussionsupporting
confidence: 90%
“…However, one study reported an increase in LDL and a decrease in HDL [42]. Our study showed an increase in HDL levels compared with pre-Ramadan level of HDL, which agrees with different studies reported for other populations [12], [43], [44]. Overall positive effects of Ramadan on lipid profile in Type 2 diabetic patients have been observed in the current study.…”
Section: Resultssupporting
confidence: 92%
“…Khafaji et al reported an increase in triglycerides (TG) and a decrease in the level of total cholesterol (TC) [11]. Hadi et al on the other hand found an increase in the level of cholesterol and no effect on the level of TG [12]. However, some other studies found no change or found only decreased levels of cholesterol during fasting [11], [13].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis compared nutritional data from four studies conducted in different regions [ 24 ]. Studies from the Greater Middle East region (Algeria and Tunisia) reported increased fat intake and decreased carbohydrate consumption during Ramadan [ 25 , 26 ]. Studies from South-East Asian countries showed increased and decreased fat intake during Ramadan in Singapore and Indonesia, respectively [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%